1967
DOI: 10.1002/ar.1091580105
|View full text |Cite
|
Sign up to set email alerts
|

The development of the arterial outflow tract in the chick embryo heart

Abstract: Bloodstream flow patterns have been outlined in the arterial outflow tract (ventricular outflow tract and bulbus arteriosus) of the chick embryo heart during the period in which septation takes place. Hemodynamic factors underlying flow changes during this period are discussed.The mapping of flow patterns did not support the concept of a conoventricular flange reported previously. Septation was found to take place between two separate and discrete bloodstreams. The cellular nature of the aorticopulmonary septu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…It may be argued that this swelling interferes with the flow profile that causes an error in the velocity data. Observations in the chick embryo have indicated that conotruncal flow is laminar but not turbulent in the stage of development of the conotruncal swelling (3,6). In the rat embryo, it was observed under a microscope that the conotruncal region was fully patent during ventricular ejection and almost completely obliterated during ventricular diastole; this finding was Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be argued that this swelling interferes with the flow profile that causes an error in the velocity data. Observations in the chick embryo have indicated that conotruncal flow is laminar but not turbulent in the stage of development of the conotruncal swelling (3,6). In the rat embryo, it was observed under a microscope that the conotruncal region was fully patent during ventricular ejection and almost completely obliterated during ventricular diastole; this finding was Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Herein we indicate that measurement of blood pressure in the rat embryo is feasible, but with some limitations, and that there may be qualitative hemodynamic differences between the rat and chick embryos. (Pediatr Res 23: 200-205,1988) While searching for the basic mechanism of normal and abnormal morphogenesis of the cardiovascular system, several investigators have been trying to correlate the change of hemodynamics or rheology of the cardiovascular system to morphogenesis (1)(2)(3)(4)(5). These studies have revealed that several teratogenic factors alter the hemodynamics (6-12).…”
mentioning
confidence: 99%
“…IT IS a traditional view that spiral streams of blood mold the primary heart tube during its development, and play a major role in the formation of the ventricular, bulbar, and aortico-pulmonary septa (Spitzer, 1923;Bremer, 1932;Goerttler, 1955;Barthel, 1960;De Vries et al, 1962;Jaffee, 1962Jaffee, , 1963Jaffee, , 1965Jaffee, , 1966Jaffee, , 1967. Experiments have been carried out to test this hypothesis.…”
mentioning
confidence: 99%
“…Two spiral streams have been described, based on observations of the moving blood cells within the primitive heart (Bremer, 1932;Jaffee, 1962Jaffee, , 1963Jaffee, , 1965Jaffee, , 1966Jaffee, , 1967. This method of evaluation, however, is inadequate for tracing the entire course of the streams in the heart tube, and is subject to error.…”
mentioning
confidence: 99%
“…Cell junctions between VECs are also similar to those of arterial endothelial cells. VECs however seem to be phenotypically different from arterial endothelial cells (Jaffee, 1967), based on the observation that VECs originate developmentally from sources different from arterial endothelial cells. In addition, VECs are oriented circumferentially across leaflets, perpendicular to the direction of the blood flow, in contrast to vascular endothelium, which aligns parallel to flow (Deck, 1986;Schoen, 2008).…”
Section: Endothelial Cellsmentioning
confidence: 99%